Vitamin B1 and B6 nutritional status in elite Polish athletes - Szczepanska, B.; Malczewska-Lenczowska, J.; Michalski, R. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Vitamins B1 and B6 are necessary in the energy-producing pathways of the body. There is evidence that marginal or subclinical deficiencies of these vitamins might cause a decline in athletic performance; therefore the purpose of the present study was to examine of B1 and B6 vitamin status and estimate the frequency of the risk of a deficiency of both vitamins in elite Polish athletes representing different sports. In the period of 2000-2014, the risk of vitamin B1 deficiency was determined in 814 healthy athletes: 515 males and 299 females (2875 total measurements, 1896 in males and 979 in females), and risk of vitamin B6 deficiency in 894 athletes: 567 males and 327 females (3290 total measurements, 2142 in males and 1148 in females). To assess vitamin B1 and B6 status the enzymatically determined activation coefficients (AC) of erythrocyte transketolase (ETK) for vitamin B1 and of erythrocyte aspartic aminotransferase (EAST) for vitamin B6, were used. The cutoff values > 1.25 for ETK AC and > 1.85 for EAST A were accepted as criteria of deficit of vitamin B1 and B6, respectively. The ranges of ETK AC 1.20- 1.25 for vitamin B1 and of EAST AC 1.7-1.85 for vitamin B6 were classified as marginal deficiency. The Shapiro-Wilk test was applied to test normality of the data and the ANOVA with the post hoc Tukey`s HSD test was used for statistical analysis. The risk of vitamin B1 deficiency was found in only 2% of all athletes. In the case of vitamin B6 the risk of deficiency was higher, 11%, while its marginal deficiency was observed in 22% of subjects. The risk of deficiency of vitamin B6 was higher than vitamin B1, both in individual years and in different sports. Athletes practising anaerobic sports were more exposed to the risk of vitamin B6 deficiency than those practising endurance disciplines. Furthermore, women were more exposed to the risk of deficiency of both vitamins than men. The relatively high prevalence of vitamin B6 risk among athletes confirms the need to monitor the nutritional status of this vitamin. The study was supported by the Ministry of Sport and Tourism of the Republic of Poland (2000-2014)